Exercise Reverses Nociceptive Sensitization, Upregulated Neuropeptide Signaling, Inflammatory Changes, Anxiety, and Memory Impairment in a Mouse Tibia Fracture Model. (September 2018) - Shi, Xiaoyou; Guo, Tian-zhi; Li, Wenwu; Sahbaie, Peyman; Rice, Kenner C.; Sulima, Agnieszka; Clark, J. David; Kingery, Wade S.
Abstract : What We Already Know about This Topic: Tibial fracture is often accompanied by allodynia, unweighting, and local and systemic inflammation. Whether injury- or pain-induced, relative immobility contributes to the development of these symptoms, and inflammatory changes are not clear. In a mouse model of tibial fracture, the effects of increased exercise and mobility, 4 weeks after the fracture, on allodynia, unweighting, inflammation, and behavioral consequences was evaluated. What This Article Tells Us That Is New: Exercise significantly improved mobility, reduced allodynia and unweighting, and attenuated behavioral consequences of anxiety and memory loss. Exercise also had a salutary effect on systemic inflammation. Of interest, suspension of exercise recapitulated allodynia, unweighting of the fractured limb, and inflammation. The results suggest that exercise can improve long-term outcomes after tibial injury in experimental models. Background: This study tested the hypothesis that ad lib running wheel exercise in a tibia fracture model of complex regional pain syndrome can reverse hindlimb nociceptive sensitization and inflammation in mice. Methods: Three weeks after tibia fracture, the cast was removed and hindlimb von Frey thresholds and unweighting were tested; the mice were then randomized to either ad lib access to a running wheel for 4 weeks or no wheel access. After 4 weeks the behavioral testing was repeated and then skin, sciatic nerve, and spinal cord tissues collected for polymerase chain reaction and enzyme immunoassay measurements of neuropeptide and inflammatory mediator levels. A similar protocol was used in fracture mice treated with exercise for 4 weeks, and then the running wheel was removed for 2 weeks. Memory and anxiety were measured in both groups with use of open-field, zero-maze, and novel-objects recognition assays. Results: At 7 weeks postfracture the mice with no wheel access exhibited hindlimb allodynia and unweighting, anxiety, memory loss, upregulated spinal neuropeptide signaling, and increased hind paw and spinal inflammatory mediator expression, but the postfracture mice allowed to exercise for 4 weeks exhibited none of these changes (n = 12/cohort). When exercise was stopped for 2 weeks after 4 weeks of running, hindlimb allodynia and unweighting were rekindled, and this nociceptive sensitization was associated with increased sciatic nerve neuropeptide levels and hind paw skin interleukin 6 and nerve growth factor expression (n = 12/cohort). Conclusions: Daily exercise reversed nociceptive sensitization, inflammation, anxiety, and memory loss after tibia fracture. Abstract : Exercise significantly improved mobility, reduced allodynia and unweighting, and attenuated behavioral consequences of anxiety and memory loss. Exercise also had a salutary effect on systemic inflammation. Of interest, suspension of exercise recapitulated allodynia, unweighting of the fractured limb, and inflammation. The results suggest that exercise can improve long-term outcomes after tibial injury in experimental models.